Heart rate and heart rate variability during adaptation to rapid time zone shift - Rusko, H. K.; Hynynen, E.; Vasankari, T. (2001)
The effect of rapid transmeridian air travel on autonomic regulation was studied by measuring supine and standing heart rate (HR) and heart rate variability (HRV) from 17 national team athletes. Before and for 10 consecutive mornings after 22-hour flight from Finland to Sydney (-9 hours) RR-data were collected each morning during a 5-min supine rest period and for 3 minutes after active standing up. RR-data were collected with Polar VNV heart rate monitors and analyzed with PPP 2.0 Software. Compared to baseline ANOVA indicated a significant increase in supine HR with a 6.8 ± 2.2 % increase in the 8th morning (p<0.05). A similar but non-significant trend was found in standing HR and HR peak after standing up. ANOVA also showed significant decreases in the supine root mean square of successive differences (RMSSD) and high frequency power (HFP). After initial increase supine HFP decreased until the 7th to 9th morning (p< 0.05). RMSSD was lowest in the 8th and 9th morning (p<0.05). A similar but non-significant trend was found in standing HFP. To investigate the overall changes in parasympathetic regulation the mean of the percentage changes from the baseline of supine HFP, standing HFP and 60/HRpeak was calculated and this mean was decreased in the 4th and from 6th to 10th morning (p< 0.01 - 0.05). We conclude that air flight and rapid time zone shift of 9 hours induced HR- and HRV-changes which lasted for 10 days. The changes seemed to be due to increased parasympathetic withdrawal that was most pronounced in the 6th - 8th morning. Individual differences in the adaptation to rapid times zone shift were great and in many athletes autonomic balance had not recovered to the baseline in 10 days. The HR- and HRV -measurements in active orthostatic test are suggested as a simple means to control the adaptation to rapid time zone shift.